Safety Effectiveness of Converting Conventional Intersections to Roundabouts: Case Study in the City of Niš - Vujanić, Milan; Savićević, Milan; Antić, Boris; Pešić, Dalibor (Promet - Traffic&Transportation, 2016)
Intersections present a big safety problem in traffic since there has been an increased risk of crashes because of conflicts in the flows intersecting. A great number of studies done in the world show that roundabouts are safer than conventional intersections since it has been recorded that after the conversion to roundabouts the number of crashes has been decreasing. The research on applying Empirical Bayes (EB) method has been conducted by using 15 two-lane intersections in the city of Niš (Serbia), which have been converted into large compact two-lane roundabouts during the period of 2005-2013. The results show that the conversion of conventional intersections into roundabouts has positive effect on reducing the number of crashes. For all intersections, the reduction of crashes is estimated at around 76% for all crashes, i.e. 80% for the crashes with injuries. For different groups of intersections the effects are determined separately.